Analysis Of Communication And Hr Implementation Of The Covid-19 Vaccination Program In The Elderly In North Musi Rawas District - Titien Kesuma; Haerawati Idris; Rostika Flora (Science Midwifery, 2022)
The study, titled "Analysis of the Implementation of the Covid-19 Vaccination Program for the Elderly in North Musi Rawas Regency," aims to determine the implementation of the COVID-19 vaccination program for the elderly in North Musi Rawas Regency.Techniques and tools for collecting data through in-depth interviews and observations, as well as using qualitative methods with case study designs, ensure that the data is presented in a complete description to describe a phenomenon observed in real-life contexts if the boundaries between phenomena and contexts do not appear clear and if multiple sources of evidence are needed. The conclusion in the study regarding the implementation of the Covid-19 vaccination program for the elderly in North Musi Rawas Regency is that it is still experiencing obstacles and that it is difficult for the elderly to get the vaccine because the long queue results in the elderly being tired and the access to vaccination sites is far, so if there is a further vaccine, it is advisable to do a door-to-door. The factors that influence this implementation are resources and communication.